The Importance of the Pirls International Assessment Program in the Educational System of Uzbekistan - Zulfiyakhan, Khakimova (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information on the importance of the Pirls International Assessment Program in the education system of our country, its implementation in general secondary schools.